Hand osteoarthritis: Differential diagnosis with inflammatory joint diseases and treatment policy - Yu. A. Olyunin (Современная ревматология, 2016)
Osteoarthritis (OA) usually affects certain joint groups selectively and the hand joints (HJ) are one of its classical locations. Hand OA is widespread in the population. In their practice rheumatologists encounter HJ injury in OA in 38% of cases. It is conventional to identify three main types of hand OA. These are 1) interphalangeal OA that may or may not be accompanied by nodulation; 2) first carpometacarpal OA; and 3) erosive OA. At the same time, the rate of clinical forms ranges from 2.0 to 6.2%; it is 4.7 to 20.4% in the elderly. Nonsteroidal antiinflammatory drugs (NSAIDs) are most commonly used to relieve pain that is the main manifestation of the disease. The risk for NSAID-related adverse gastrointestinal (GI) events is substantially reduced by the drugs that exert their effects mainly on cyclooxygenase 2. These include nimesulide in particular. Undesirable GI effects may be also considerably minimized by using NSAIDs that have both their gastroprotective and antiinflammatory activities. By suppressing pain and inflammatory changes, the recently designed NSAID amtolmetin guacil simultaneously exerts a protective effect on the GI mucosa, by elevating its nitric oxide levels.